Right place, right time : the life of a rock & roll photographer - Gruen, Bob; Thompson, Dave, 1960 January 3- (Abrams Press, 2020)
The veteran rock-and-roll photographer shares memories from nearly half a century in the industry, from his cross-country trip with the Ike and Tina Turner band to his backstage encounters with KISS.